Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1186/s12891-017-1682-2
|View full text |Cite
|
Sign up to set email alerts
|

Objective impairments of gait and balance in adults living with HIV-1 infection: a systematic review and meta-analysis of observational studies

Abstract: BackgroundGait and balance deficits are reported in adults with HIV infection and are associated with reduced quality of life. Current research suggests an increased fall-incidence in this population, with fall rates among middle-aged adults with HIV approximating that in seronegative elderly populations. Gait and postural balance rely on a complex interaction of the motor system, sensory control, and cognitive function. However, due to disease progression and complications related to ongoing inflammation, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 93 publications
(240 reference statements)
3
53
1
1
Order By: Relevance
“…NIH quality assessment tool was used to evaluate cross‐sectional studies. Inherent to the design, cross‐sectional studies automatically scored “not applicable” for question 6, 7, 10, 13 (Berner, Morris, Baumeister, & Louw, ). The studies were classified according to their quality: 0–3 low quality, 4–6 fair quality and 7–10 good quality.…”
Section: Methodsmentioning
confidence: 99%
“…NIH quality assessment tool was used to evaluate cross‐sectional studies. Inherent to the design, cross‐sectional studies automatically scored “not applicable” for question 6, 7, 10, 13 (Berner, Morris, Baumeister, & Louw, ). The studies were classified according to their quality: 0–3 low quality, 4–6 fair quality and 7–10 good quality.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have identified that the postural sway of PLHA may be compromised by several factors, in addition to being a condition present in asymptomatic individuals 11,[13][14][15] . The scholars 6,15 have suggested that increased postural oscillation is associated with manifestations of HIV in the central nervous system (CNS).…”
Section: Discussionmentioning
confidence: 99%
“…This condition can, directly or indirectly, influence postural sway, specifically in more difficult tasks 11,12 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations